Gold Single Atom Doped Defective Nanoporous Copper Octahedrons for Electrocatalytic Reduction of Carbon Dioxide to Ethylene - Zhao, Yang (2025)
Electrocatalytic CO2 reduction into high-value multicarbon products offers a sustainable approach to closing the anthropogenic carbon cycle and contributing to carbon neutrality, particularly when renewable electricity is used to power the reaction. However, the lack of efficient and durable electrocatalysts with high selectivity for multicarbons severely hinders the practical application of this promising technology. Herein, a nanoporous defective Au1Cu single-atom alloy (DeAu1Cu SAA) catalyst is developed through facile low-temperature thermal reduction in hydrogen and a subsequent dealloying process, which shows high selectivity toward ethylene (C2H4), with a Faradaic efficiency of 52% at the current density of 252 mA cm−2 under a potential of −1.1 V versus reversible hydrogen electrode (RHE). In situ spectroscopy measurements and density functional theory (DFT) calculations reveal that the high C2H4 product selectivity results from the synergistic effect between Au single atoms and defective Cu sites on the surface of catalysts, where Au single atoms promote *CO generation and Cu defects stabilize the key intermediate *OCCO, which altogether enhances C−C coupling kinetics. This work provides important insights into the catalyst design for electrochemical CO2 reduction to multicarbon products.